Currículo de ciências contábeis: desafios para adoção ao novo modelo contábil brasileiro - Carvalho, Ronaldo Fróes de (2010)
This study aims at presenting a theoretical research in which the necessity of curricular changes for the undergraduate Accounting programs are discussed as a consequence of the new accounting model adopted by the Brazilian corporate legislation, in accordance to an amendment made in 2007. The main change, in general terms, is a convergence between the Brazilian accounting standards and the international accounting standards, which their considerable divergences, particularly in relation to their principles, as compared to those adopted in Brazil. From this standpoint, this research shows the evolution of accounting rules in Brazil and abroad, finally getting into the current situation and, from the opening given by the National Curriculum Guidelines, discuss the need for changes in the curriculum of undergraduate Accounting programs, taking into consideration the curriculum content, skills and abilities to be developed in the graduates from these courses and teaching skills for the Accounting Sciences professors